2016
DOI: 10.1186/s12889-016-2813-7
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of treatment-seeking behaviors among caregivers of febrile young children: a Ugandan multiple case study

Abstract: BackgroundThe vast majority of malaria deaths in Uganda occur in children five and under and in rural areas. This study’s exploratory case study approach captured unique situations to illustrate special attributes and aspects of treatment-seeking during a malaria episode.MethodsDuring August 2010, a qualitative exploratory study was conducted in seven of Butaleja District’s 12 sub-counties. Multiple case study methodology consisting of loosely-structured interviews were carried out with eight caregivers of chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 33 publications
2
30
0
Order By: Relevance
“…Our study found the practice of polypharmacy to be common, with one in three caregivers in Butaleja reporting using multiple antimalarials to manage malaria in their children, often in combination with non-antimalarials. This practice was confirmed in a follow-up study conducted in Butaleja, and has been reported in other regions of Uganda [15, 2830]. The work by Rutebemberwa et al found a large majority of caregivers in Iganga District preferred combination therapy, but caregivers’ views about which antimalarials to start a child on varied considerably [28].…”
Section: Discussionmentioning
confidence: 59%
“…Our study found the practice of polypharmacy to be common, with one in three caregivers in Butaleja reporting using multiple antimalarials to manage malaria in their children, often in combination with non-antimalarials. This practice was confirmed in a follow-up study conducted in Butaleja, and has been reported in other regions of Uganda [15, 2830]. The work by Rutebemberwa et al found a large majority of caregivers in Iganga District preferred combination therapy, but caregivers’ views about which antimalarials to start a child on varied considerably [28].…”
Section: Discussionmentioning
confidence: 59%
“…These findings confirm reports that private outlets continue to fill the gap between home management, CHWs and public facilities. Regular ACT stock-outs, frequent referrals to private vendors by public health providers to purchase anti-malarials, and poor service at public health facilities have been cited as common reasons for visiting private outlets in Butaleja [ 7 ]. Further, only a third of caregivers in Butaleja reported that ACT was easy to find in their community and one in six believed ACT was affordable.…”
Section: Discussionmentioning
confidence: 99%
“…Examples of such initiatives include the dissemination of first-line anti-malarial artemisinin-based combination therapy (ACT) cost-free from all public health facilities; the introduction of the Integrated Community Case Management Programme (iCCM) in mid-2010 to bring diagnostics and treatment closer to the community; the introduction of the Affordable Medicines Facility-Malaria (AMFm) in Spring 2011 to improve access to a range of ACT from licensed public and private outlets; the ban of resistant anti-malarials; the training of public providers; sensitization meetings with district-level leaders; and information, education and communication campaigns to improve household awareness [ 1 , 4 ]. Despite these initiatives, translating policy into practice to ensure universal access to ACT has been challenging in rural areas due to regular stock-outs of anti-malarials at public facilities, dispensing of non-first-line anti-malarial therapy at health facilities, and limited access to licensed private outlets supported by the AMFm scheme [ 5 7 ]. At the time of this study, it was also recognized that the delivery of iCCM was complex, requiring both providers and recipients of care to be fully engaged for desired outcomes to be achieved [ 6 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, nearly half a million (429 000) deaths were caused by malaria, and more than 92% 0f these deaths have been happened in sub-Sahara African countries [2]. Consequently, malaria is still the leading public health problem in developing nations and it predominately affects pregnant mothers and under-ve children [3].…”
Section: Introductionmentioning
confidence: 99%